A New Normal: Young Men of Color, Trauma and Engagement in Learning - Joni M. Schwartz (Adult Education Research Conference, 2012)
This phenomenological study examined trauma experienced by young men of color, trauma‘s effect on engagement in college, and the young men‘s willingness to access counseling. The theoretical and methodological frameworks are Critical Race Theory (CRT) and Cultural Historical Activity Theory (CHAT) respectively. The findings from the study presented in this paper suggest that young men have a ―lived experience‖ of trauma that they perceive as normal which impacts their engagement in learning.